The Study of Unprecedented Tubular Channels Formation in Alkyl-Substituted Oxamide Oxime Metal Complexes - Chumakov, Yurii; Luneau, Dominique; Yüksel, Fatma; Ahsen, Vefa; Gumus, Gulay; Gurol, Ilke (Int Union Crystallography, 2007)
[No abstract available]
Keywords: oxamide oxime metal complexes; tubular channels; conformational analysis